Abiraterone acetate in combination with androgen deprivation therapy compared to androgen deprivation therapy only for metastatic hormone-sensitive prostate cancer. - Sathianathen, Niranjan J.; Oestreich, Makinna C.; Brown, Sarah Jane; Gupta, Shilpa; Konety, Badrinath R.; Dahm, Philipp; Kunath, Frank (Cochrane Database of Systematic Reviews, 2020)
BACKGROUND: Systemic androgen deprivation therapy (ADT), also referred to as hormone therapy,ÃÂ has long been the primary treatment for metastatic prostate cancer. Additional agents have been reserved for the castrate-resistant disease stage when ADT start becoming less effective. Abiraterone is an agent with an established role in that disease stage, which has only recently been evaluated in the hormone-sensitive setting. OBJECTIVES: To assess the effects of early abiraterone acetate, in combination with systemic ADT, for newly diagnosed metastatic hormone-sensitive prostate cancer. SEARCH METHODS: We searched CENTRAL, MEDLINE, Embase, six other databases, two trials registries, grey literature, and conference proceedings, up to 15 May 2020. We applied no restrictions on publication language or status. SELECTION CRITERIA: We included randomized trials, in which men diagnosed with hormone-sensitive prostate cancer were administered abiraterone acetate and prednisolone with ADT or ADTÃÂ alone. DATA COLLECTION AND ANALYSIS: Two review authors independently classified studies and abstracted data from the included studies. We performed statistical analyses using a random-effects model. We rated the quality of evidence according to the GRADE approach. MAIN RESULTS: The search identified two randomized controlled trials (RCT), with 2201 men, who were assigned to receive either abiraterone acetate 1000 mg once daily and low dose prednisone (5mg) in addition to ADT, or ADT alone. In the LATITUDE trial, the median age and range of men in the intervention group was 68 (38 to 89) years, and 67 (33 to 92) years in the control group. Nearly all of the men in thisÃÂ study (97.6%) had prostate cancer with a Gleason score of at least 8 (ISUP grade group 4). Primary outcomes The addition of abiraterone acetate to ADT reduces the probability of death from any cause compared to ADT alone (hazard ratio [HR] 0.64, 95% confidence interval [CI] 0.56 to 0.73; 2 RCTs, 2201 men; high certainty of evidence); this corresponds to 163 fewer deaths per 1000 men with hormone-sensitive metastaticÃÂ prostate cancerÃÂ (210 fewer to 115 fewer) at five years. Abiraterone acetate in addition to ADT probably results in little to no differenceÃÂ in quality of life compared to ADT alone, measured with the Functional Assessment of Cancer Therapy-prostate total score (FACT-P; range 0 to 156; higher values indicates better quality of life),ÃÂ at 12 months (mean difference [MD] 2.90 points, 95% CI 0.11 to 5.60; 1 RCT, 838 men; moderate certainty of evidence). Secondary outcomes Abiraterone plus ADT increases the risk of grades III to V adverse events compared to ADT alone (risk ratio [RR] 1.34, 95% CI 1.22 to 1.47; 1 RCT, 1199 men; high certainty of evidence); this corresponds to 162 more grade III to VÃÂ events per 1000 men with hormone-sensitive metastaticÃÂ prostate cancerÃÂ (105 more to 224 more) at a median follow-up of 30ÃÂ months. Abiraterone acetate in addition to ADT probably reduces the probability of death due to prostate cancer compared to ADT alone (HR 0.58, 95% CI 0.50 to 0.68; 2 RCTs, 2201 men; moderate certainty of evidence). This corresponds to 120 fewer death from prostate cancer per 1000 men with hormone-sensitive metastaticÃÂ prostate cancerÃÂ (95% CI 145 fewer to 90 fewer) afterÃÂ a median follow-up of 30 months. The addition of abiraterone acetate to ADT probably decreases the probability of disease progression compared to ADT alone (HR 0.35, 95%CI 0.26 to 0.49; 2 RCTs, 2097 men; moderate certainty of evidence). This corresponds to 369 fewer incidences of disease progression per 1000 men with hormone-sensitive metastaticÃÂ prostate cancerÃÂ (456 fewer to 256 fewer)ÃÂ after a median follow-up of 30 months. The addition of abiraterone acetate to ADT probably increases the risk of discontinuing treatment due to adverse events compared to ADT alone (RR 1.50, 95% CI 1.17 to 1.92; 1 RCT, 1199 men; moderate certainty of evidence). This corresponds to 51 more men (95% CI 17 more to 93 more) discontinuing treatment because of adverse events per 1000 men treated with abiraterone acetate and ADT compared to ADT alone afterÃÂ a median follow-up of 30 months. AUTHORS' CONCLUSIONS: The addition of abiraterone acetate to androgen deprivation therapy improves overall survival but probably not quality of life. ItÃÂ probably also extends disease-specific survival, and delays disease progression compared to androgen deprivation therapy alone. However, the risk of grades III to V adverse events is increased, and probably, so is the risk of discontinuing treatment due to adverse events.
EVALuna2:476855